Collateralized borrowing around the world: Insights from the World Bank Enterprise Surveys. (29th September 2020) - Fan, Yuting; Nguyen, Ha; Qian, Rong
Abstract: Despite an important role of collateralized borrowing in corporate finance and financial economics, there has been little empirical research that systematically documents the prevalence and correlates of collateralized borrowing across countries. We filled this gap by investigating firms' collateralized borrowing in 131 countries between 2005–2017 using the World Bank Enterprise Surveys. Overall, 77% of loans require collateral, and the median loan‐to‐collateral value is 60%. While small firms and loans from non‐bank financial institutions are less often associated with collateral, when collateral is pledged, the type of collateral assets is strongly correlated with the loan‐to‐value ratio. When more illiquid and indivisible assets such as land and buildings are pledged as collateral, higher collateral value is required.